Biochar from co-pyrolysis of biological sludge and sawdust in comparison with the conventional filling media of vertical-flow constructed wetlands for the treatment of domestic-textile wastewater - Mariem Ayadi; Davide Passaseo; Giulia Bonaccorso; Michelangelo Fichera; Lapo Renai; Lorenzo Venturini; Ilaria Colzi; Donatella Fibbi; Massimo Del Bubba (Water Science and Technology, 2024)
A biochar from co-pyrolysis of a mixture of sawdust and biological sludge (70/30, w/w), providing a high environmental compatibility in terms of water leachable polycyclic aromatic hydrocarbons and inorganic elements, together with a remarkable surface area (389 m2/g), was integrated into laboratory-scale vertical-flow constructed wetlands (VF-CWs), planted with Phragmites australis and unplanted. Biochar-filled VF-CWs have been tested for 8 months for the refining of effluents from the tertiary clariflocculation stage of a wastewater treatment plant operating in a mixed domestic-industrial textile context, in comparison with systems filled with gravel. VF-CW influents and effluents were monitored for chemical oxygen demand (COD), nitrogen and phosphorus cycles, and absorbance values at 254 and 420 nm, the latter as rapid and reliable screening parameters of the removal of organic micropollutants containing aromatic moieties and/or chromophores. Biochar-based systems provided a statistically significant improvement in COD (Δ = 22%) and ammonia (Δ = 35%) removal, as well as in the reduction of UV–Vis absorbance values (Δ = 32–34% and Δ = 28% for 254 and 420 nm, respectively), compared to gravel-filled microcosms. The higher removal of organic was mainly attributed to the well-known adsorption properties of biochars, while for nitrogen the biological mechanisms seem to play a predominant role. HIGHLIGHTS Biochar from sawdust and sludge 70/30 (w/w) was produced and characterized.; This biochar was used as filling media of vertical-flow constructed wetlands (CWs).; Planted and unplanted CWs filled with biochar were compared to gravel-based CWs.; Organic matter, UV–Vis absorption, nitrogen and phosphorus cycles were monitored.; Biochar-based CWs showed 22–35% higher removal, depending on the parameter studied.;